Characterization and migration of oil and solids in oily sludge during centrifugation. Issue 10 (19th May 2018) - Wang, Jun; Han, Xu; Huang, Qunxing; Ma, Zengyi; Chi, Yong; Yan, Jianhua
ABSTRACT: The migration behaviors of oil, water and solids in sludge during centrifugation were elaborated. Size distribution, surface topography and lypohydrophilic properties were studied in detail. The average size of solids was 61 μm in original sludge, 31 μm in upper layer and 235 μm in bottom layer. The result shows that solvent is essential to separate oil phase into molecular light and weight fractions during centrifugation. With solvent/oil ratio increases from 1:2, 1:1, 2:1 to 5:1, molecular weight in upper layer decreases from 1044, 1043, 1020 to 846 combined with that in bottom layer increases. A model was proposed to calculate the oil residue content in solid phases after sedimentation. The findings of this paper provide information for optimizing the oil recovery and clean treatment.